Total Physical Response as an Instructional Strategy for Enhancing Vocabulary Learning Among Young EFL Learners - Andrieco Septya Firmansyah; Feri Ferdiyanto; Moh. Hifdil Islam (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study aimed to determine the effectiveness of the Total Physical Response (TPR) method in improving the English vocabulary mastery of young EFL learners at SD Zainul Hasan Genggong, Probolinggo. Employing a quantitative approach with a one-group pre-test and post-test design, the research involved 28 sixth-grade students selected through purposive sampling. Data were collected using a 20-item vocabulary test administered before and after the TPR intervention, and analyzed using descriptive statistics. The findings revealed a significant improvement in students' vocabulary mastery. Prior to the treatment, the pre-test mean score was only 12.50, with most students categorized as poor. Following the implementation of the TPR method, the post-test mean score surged to 88.57, shifting the majority of students into the excellent category. This substantial increase of 76.07 points indicates that integrating physical movements with verbal instructions effectively enhances vocabulary retention and comprehension. In conclusion, the TPR method is highly effective in improving young learners' English vocabulary mastery by transforming passive memorization into an interactive, engaging, and meaningful learning experience.